2009
DOI: 10.2503/jjshs1.78.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Explant Source and Dark-preconditioning on Adventitious Bud Formation in Neofinetia falcata H. H. Hu in vitro

Abstract: Tissue culture methods were investigated for propagation of the epiphytic orchid Neofinetia falcata H. H. Hu. The protocorms were divided into upper and lower portions and cultured. An average of 1.0-1.7 plantlets per explant were derived from upper portions which had survived at frequencies at 10-30%. Plantlets that developed from protocorms were cultured to increase the survival rate. All explants derived from upper portions of the plantlets survived, but explants from lower portions of plantlets did not. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In N. falcata, treatment with AOPP controlled phenol compound biosynthesis in the explants and promoted adventitious bud formation, which were similar to the effects of dark preconditioning (Mitsukuri et al, 2009); however, dark preconditioning needs to find the conditioning period of each plant. In our previous study, dark preconditioning reduced the explant survival rate and preconditioned plantlets formed 5.1 buds per survived explant (Mitsukuri et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In N. falcata, treatment with AOPP controlled phenol compound biosynthesis in the explants and promoted adventitious bud formation, which were similar to the effects of dark preconditioning (Mitsukuri et al, 2009); however, dark preconditioning needs to find the conditioning period of each plant. In our previous study, dark preconditioning reduced the explant survival rate and preconditioned plantlets formed 5.1 buds per survived explant (Mitsukuri et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
“…(Wang et al, 1994), Psidium guajava (Meghwal et al, 2001), and Mangifera indica (Sharma and Singh, 2002), which increases bud formation. In our previous study, we found that dark preconditioning was an effective treatment for browning control and promotion of bud formation in N. falcata (Mitsukuri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations